Heterogeneous Expression and Subcellular Localization of Pyruvate Dehydrogenase Complex in Prostate Cancer - Nunes-Xavier, Caroline E.; Mingo, Janire; Emaldi, Maite; Flem-Karlsen, Karine; Mælandsmo, Gunhild M.; Fodstad, Øystein; Llarena, Roberto; López, José I.; Pulido, Rafael (Frontiers in Oncology, 2022)
Background: Pyruvate dehydrogenase (PDH) complex converts pyruvate into acetyl-CoA by pyruvate decarboxylation, which drives energy metabolism during cell growth, including prostate cancer (PCa) cell growth. The major catalytic subunit of PDH, PDHA1, is regulated by phosphorylation/dephosphorylation by pyruvate dehydrogenase kinases (PDKs) and pyruvate dehydrogenase phosphatases (PDPs). There are four kinases, PDK1, PDK2, PDK3 and PDK4, which can phosphorylate and inactivate PDH; and two phosphatases, PDP1 and PDP2, that dephosphorylate and activate PDH. Methods: We have analysed by immunohistochemistry the expression and clinicopathological correlations of PDHA1, PDP1, PDP2, PDK1, PDK2, PDK3, and PDK4, as well as of androgen receptor (AR), in a retrospective PCa cohort of patients. A total of 120 PCa samples of representative tumor areas from all patients were included in tissue microarray (TMA) blocks for analysis. In addition, we studied the subcellular localization of PDK2 and PDK3, and the effects of the PDK inhibitor dichloroacetate (DCA) in the growth, proliferation, and mitochondrial respiration of PCa cells. Results: We found heterogeneous expression of the PDH complex components in PCa tumors. PDHA1, PDP1, PDK1, PDK2, and PDK4 expression correlated positively with AR expression. A significant correlation of PDK2 immunostaining with biochemical recurrence and disease-free survival was revealed. In PCa tissue specimens, PDK2 displayed cytoplasmic and nuclear immunostaining, whereas PDK1, PDK3 and PDK4 showed mostly cytoplasmic staining. In cells, ectopically expressed PDK2 and PDK3 were mainly localized in mitochondria compartments. An increase in maximal mitochondrial respiration was observed in PCa cells upon PDK inhibition by DCA, in parallel with less proliferative capacity. Conclusion: Our findings support the notion that expression of specific PDH complex components is related with AR signaling in PCa tumors. Furthermore, PDK2 expression associated with poor PCa prognosis. This highlights a potential for PDH complex components as targets for intervention in PCa.